(untitled) (UUM Journal of Legal Studies, 2022)
Flexible work arrangements are common during the COVID-19 pandemic as a result of the movement restriction and the closure of the economic sector. Among the flexibility practices is the implementation of remote working, in particular, working from home (WFH) where employees are physically working outside and remote from their organisations. The mandated WFH has changed the working scenario without confirming whether employers and employees are prepared for this new norm. However, the WFH arrangement requires legal consideration as its arrangement needed a legal predicament. The concern over WFH must be addressed on the grounds of managerial rights and boundaries besides determining the rights of employees while working remotely. From the legal viewpoint, there is a question of whether the existing labour law in Malaysia is accommodating to the WFH practice. Hence, this paper aims to examine the employment-related matters concerning WFH practice in Malaysia on employment terms like wages and leaves, matters on safety and health, social security, and confidentiality and security of information. This study applied a doctrinal approach using authoritative legal texts in solving the legal problems that arise from WFH. The analysis of legal provisions and case studies were employed to present the benefits of the employment relationship and industrial relations in the changing employment landscape and work culture linked to WFH.